Eubostrichopsis johnpearsei n. gen., n. sp., the first stilbonematid nematode (Nematoda, Desmodoridae) from the US West Coast - Ott, Jörg A.; Pröts, Philipp (Zootaxa, 2021)
A new genus of the marine Stilbonematinae (Nematoda, Desmodoridae) is described from the Pacific coast of the United States of America. The worms inhabit the sulfidic sediment among the roots of the surfgrass Phyllospadix sp. in the rocky intertidal. The ectosymbiotic coat is of a new type for Stilbonematinae. It consists of rod-shaped bacteria pointed at both poles densely attached with one pole to the host cuticle. This is the first report of this symbiotic nematode subfamily from the US West Coast.